PELATIHAN PENULISAN ESAI SEDERHANA DI YAYASAN AL-KAMILAH SERUA DEPOK - Wiwiek Rukmi Dwi Astuti; Yuliani Widianingsih; Sindy Yulia Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2021)
In language skills, writing is the last and most difficult skill compared to other abilities. Writing takes a long time and a strong internal motivation to complete the writing that has been started. Likewise with students at the Al-Kamilah Serua Depok Foundation who also experienced difficulties in developing simple writing or essays. Therefore, the PKM proposing team was here to provide simple essay writing training for junior high and high school students at the Al-Kamilah Serua Depok Foundation. The purpose of this activity is to increase the students' interest in writing and to produce a joint essay from the thoughts of the students at the Al-Kamilah Serua Foundation, Depok. The method of implementing this training is the method of lecturing and brainstorming a simple essay that is carried out offline at the foundation's location while still implementing the Covid-19 health protocol. Another method is the online lecture method through a virtual space on google meet. The result of this PKM activity is a simple short essay that is made jointly by students, increasing the knowledge and motivation of students at the Al-Kamilah Serua Depok Foundation in writing simple essays.